Resource Assessment of Oroxylum indicum in Northern Indian States of Uttarakhand, Uttar Pradesh, Punjab and Haryana - Tamta, B. P.; Uniyal, Sushmita; Ghosh, Rajarshi (International Journal of Economic Plants, 2024)
This study was undertaken from April, 2016 to March, 2018 in different forest divisions of Uttarakhand, Uttar Pradesh, Haryana, and Punjab to assess and map the distribution and population status of Oroxylum indicum that can be developed into a readily accessible database for further conservation efforts, either in-situ or ex-situ, given that the species is gradually depleting from its natural habitat due to unscientific collection practices, exploitation by uprooting of entire trees to meet the high demand for its raw materials in pharmaceuticals, perfumery, and incense industries. An extensive survey was conducted in different forest divisions of these four Northern Indian states for estimating the distribution and quantifying population of O. indicum. Data on different parameters like frequency, density, abundance, location, altitude, habitat, along with brief identifying features, were noted as per Curtis and McIntosh (1950) after laying down quadrats and transects randomly. Subsequently, geo-referenced maps were prepared showing the surveyed areas that were studied. Results of the study indicate occurrence of the species in 51 locations across 15 forest divisions of Uttarakhand, 13 locations across 02 forest divisionsof Haryana, 12 locations in 04 forest divisions of Punjab, and 17 locations across 9 forest divisions of Uttar Pradesh. This information will assist formulation of conservation plans and aid sustainable management of this valuable medicinal tree in these Northern Indian states.